Prevalence and risk factors for urinary and fecal incontinence in brazilian women - Amaro, João Luiz [UNESP]; Macharelli, Carlos Alberto [UNESP]; Yamamoto, Hamilto Akihissa [UNESP]; Kawano, Paulo Roberto [UNESP]; Padovani, Carlos Roberto [UNESP]; Agostinho, Aparecido Donizeti [UNESP] (Sociedade Brasileira de Urologia, 2009)
Objective: To evaluate prevalence and risk factors of fecal and urinary incontinence (UI) in Brazilian women. Material and Methods: 685 women older than 20 years of age answered a questionnaire about urinary and fecal symptoms, clinical and obstetric antecedents. They were grouped according to presence or absence of UI. Results: Urinary and fecal incontinence was reported in 27% and 2% of cases, respectively. Mean age of incontinent women was significantly higher than continent ones. Incontinent women had a mean number of micturitions significantly higher than the continent ones. on average, incontinent women had higher rate of pregnancies and vaginal delivery when compared to the continent ones. Body mass index (BMI) was significantly higher in incontinent participants and in women with no UI complaints (27.35 vs. 24.95, p < 0.05). Fecal incontinence prevalence was 2% and occurred exclusively in patients with UI. Conclusions: Vaginal delivery and high BMI have been identified as risk factors for UI development while aging and number of pregnancies may be correlated factors.
Keywords: urinary incontinence; fecal incontinence; female; prevalence